Evidence for NADPH oxidase activation by GPR40 in pancreatic β-cells - Gabriela Nunes Marsiglio-Librais; Eloisa Aparecida Vilas-Boas; Christopher Carlein; Markus Daniel Alexander Hoffmann; Leticia Prates Roma; Angelo Rafael Carpinelli (Redox Report, 2020)
Objective: Investigate the involvement of the fatty acids receptor GPR40 in the assembly and activation of NADPH oxidase and the implications on pancreatic β-cell function. Methods: BRIN-BD11 β-cells were exposed to GPR40 agonist (GW9508) or linoleic acid in different glucose concentrations. Superoxide and H2O2 were analyzed, respectively, by DHE fluorescence and by fluorescence of the H2O2 sensor, roGFP2-Orp1. Protein contents of p47phox in plasma membrane and cytosol were analyzed by western blot. NADPH oxidase role was evaluated by p22phox siRNA or by pharmacological inhibition with VAS2870. NOX2 KO islets were used to measure total cytosolic calcium and insulin secretion. Results: GW9508 and linoleic acid increased superoxide and H2O2 contents at 5.6 and 8.3 mM of glucose. In addition, in 5.6 mM, but not at 16.7 mM of glucose, activation of GPR40 led to the translocation of p47phox to the plasma membrane. Knockdown of p22phox abolished the increase in superoxide after GW9508 and linoleic acid. No differences in insulin secretion were found between wild type and NOX2 KO islets treated with GW9508 or linoleic acid. Discussion: We report for the first time that acute activation of GPR40 leads to NADPH oxidase activation in pancreatic β-cells, without impact on insulin secretion.